11x-13=8x+7

Simple and best practice solution for 11x-13=8x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-13=8x+7 equation:


Simplifying
11x + -13 = 8x + 7

Reorder the terms:
-13 + 11x = 8x + 7

Reorder the terms:
-13 + 11x = 7 + 8x

Solving
-13 + 11x = 7 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-13 + 11x + -8x = 7 + 8x + -8x

Combine like terms: 11x + -8x = 3x
-13 + 3x = 7 + 8x + -8x

Combine like terms: 8x + -8x = 0
-13 + 3x = 7 + 0
-13 + 3x = 7

Add '13' to each side of the equation.
-13 + 13 + 3x = 7 + 13

Combine like terms: -13 + 13 = 0
0 + 3x = 7 + 13
3x = 7 + 13

Combine like terms: 7 + 13 = 20
3x = 20

Divide each side by '3'.
x = 6.666666667

Simplifying
x = 6.666666667

See similar equations:

| (4x^2-13x-5)%(x-2) | | h(x)=0.04x^2-3.5+100 | | 15a+5b=85 | | 4x+64x^2=0 | | 9b^2-Z=103 | | 7x^2-4x-2=0 | | -7(-1.75+-0.125y)-y=13 | | 4(3a+3)-(4a+6)=15 | | p=13-6 | | 12n+4(n+4)-4(n+1)= | | 12x=15-3x | | 24=-2c | | 48=-4h | | 1-49y^2=0 | | 7(4.4+0.2y)-4y=-7 | | r-6=-10 | | 2/(3(x^(4/3))) | | 100,000*x/9500,000=0.01 | | 10x-2x=x-8 | | 2/(3x^(4/3)) | | 4(2x-3)=1 | | 6=-3+a | | -11=v-7 | | 1+33.1x=4x-10 | | b-9=4 | | 4+b=12 | | 35.28/6.3 | | y=33.1x+1 | | 1x+.2x=246 | | 7/10-3/5= | | 2x-7=11-7 | | 6-2=2+z-2 |

Equations solver categories